Inserção profissional de egressos do PIBID: desafios e aprendizagens no início da docência - Gonçalves, Gláucia Signorelli de Queiroz (2016)
This research falls within the field of teacher education and by analyzing the process of professional insertion of graduates of the Institutional Program of initiation to Teaching-Pibid, intended to bring contributions to the understanding of this crucial phase of the professional cycle: the beginning of the career. The Pibid, a program proposed by MEC/Capes for the improvement and enhancement of teacher training for basic education, aims at supporting the initiation into teaching of graduate students in order to enhance the teaching profession, contribute to the increase of the quality of basic education, and enhance the integration between theory and practice and between University and school. It was assumed that Pibid, by bringing the idea of integrated initial formation to primary schools, extends the coexistence of undergraduates with the teaching practice, boosts the initial formation and mitigates the adverse conditions faced by the early career teachers. It is known that the professional insertion of teachers is almost always a period of uncertainty, instability and tension, because it represents the beginning of the professional activities and, at the same time, the passage to adulthood and support for beginners are rare at this stage. The investigation used the qualitative approach, with data collected through focus groups with twelve beginning teachers, ex-pibidians and recent grads of the course in Pedagogy of a Federal University of the State of Minas Gerais; questionnaire for personal and professional characterization of the participants; semi-structured interviews with seven directors and supervisors of the primary schools where these teachers work; and documental analysis of the pedagogic political project of the training institution. The literature review included theorists as Nóvoa (2009a, 2009b, 2011, 2013), Marcelo Garcia (1999, 2010), Vaillant and Marcelo Garcia (2012), Imbernón (2011), Zeichner (2010), Papi (2011), Nono (2011) among others, discussing the initial formation and the early career of the teachers, which have allowed to know the paths that the beginning teachers traverse from training until the moment they enter the schools. For data analysis, was adopted the method named by André (1983) as Prose Analysis and the topics and themes raised have allowed to formulate three categories: the point of view of novice teachers on initial formation; the point of view of beginners on professional insertion; from beginners to experienced: the construction of the professional component of these teachers. The data revealed that the beginning was marked by difficulties and tensions, but at the same time, discovery and learning. It was considered that both the initial training in the course of pedagogy, and the participation in the Pibid, were essential to professional insertion, due to the configuration that both theory and practice, and the research have been gaining during the formative process, made explicit by the movement action/reflection/action, facilitated by the integration between the university and the school